Ketika harapan menjadi tekanan: ekspektasi orang tua dan kecemasan performa - Hoirunnurmalasari; Hutahaean, Erik Saut H; Muzzamil, Ferdy (Fakultas Psikologi Universitas Hang Tuah, 2025)
Parental expectations can affect psychological health such as anxiety, fear of failure and depression, with a focus on how parental expectations affect the anxiety levels of individuals undergoing physical training. This study used a quantitative approach with a correlational method to analyze data collected from 155 respondents. The results showed a significant positive correlation between perceptions of parental expectations and performance anxiety. Higher parental expectations were associated with increased levels of anxiety in participants. This relationship suggests that pressure to meet parental expectations can lead to increased anxiety, which can ultimately affect participant performance during physical training. This study highlights the importance of understanding the psychological impact of parental expectations on individuals in stressful environments. Parents are expected to provide support and realistic expectations to help reduce anxiety and improve their children's performance outcomes.